PEMANFAATAN MEDIA E-LEARNING BAGI MAHASISWA PRODI PENDIDIKAN SEJARAH UNIVERSITAS PGRI SUMATERA BARAT - Marsyanda Nadilla; Felia Siska; Meri Erawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by media because learning is a crucial factor in improving the quality of learning. This is due to technological developments in education, which demand efficiency and effectiveness in learning. To achieve optimal efficiency and effectiveness, one effort that needs to be made is to reduce, or even eliminate, the dominance of verbal-based lesson delivery systems by utilizing learning media. The purpose of this research is to describe the use of e-learning for students in the History Education Study Program at Universitas PGRI Sumatera Barat. This is a descriptive study with a qualitative approach. It aims to reveal the circumstances and facts of events that occurred during the research. The results of this study with several students in the History Education Study Program at Universitas PGRI Sumatera Barat show that most students stated that e-learning was very helpful in accessing materials and submitting assignments. However, some complained about difficulty accessing the system due to technical issues. Some students also felt they did not understand the material optimally because they were not used to studying independently through digital media. This shows that although e-learning offers various conveniences, there are still challenges that must be overcome for its use to be truly effective in supporting the learning process. Keywords: Media, E-Learning, Students